IMPROVEMENT OF OPTIMAL MANAGEMENT OF THE CITY ELECTRIC TRANSPORT ELECTRIC BRAKING ENERGY DISTRIBUTION AND USE - PAYANOK, OLEKSANDR; BABIY, SERGIY; PROCENKO, DMYTRO; GRANYAK, VALERY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper presents the results of experimental measurements at the traction substations of the city electric transport МЕ "Vinnytsia Transport Company", an analysis of the electric (regenerative) braking energy distribution and use modes, generalization and distribution of the obtained measurement results to the entire system of the traction power network. During the research, was confirmed the fact that the rectified voltage values at some traction substations in the city of Vinnytsia exceed the established normative value even in the recovery absence, which complicates the use of regenerative braking modes on individual sections of the contact network and requires the search for other options for the distribution and electric braking energy use. The implementation of regenerative braking modes in the conditions of power supply of urban electric transport depends on the peculiarities of its power system operation. It consists in the fact that traction networks and substations of urban ground electric transport operate under conditions significantly different from the conditions of stationary power electrical installations operation. Power supply systems of urban electric transport as a whole and especially individual feeder zones of contact network electrified sections are characterized by load unevenness. This is explained by: uneven power consumed by electric city transport (starting according to automatic characteristics, coasting, braking); different speeds of trams and trolleybuses, as a result, different consumed energy; the dependence of the traction substations feeders load location of electric transport on the power supply area; the number and variety of types of transport used in the electric economy; their traffic intensity and the nature of the traffic schedule; transport management technique and its type and other factors.Criteria for evaluating the energy efficiency of electric braking modes have been formed and summarized in order to increase the efficiency of electric braking of the electrotechnical complex "power supply system - electric transport of the city" energy use. Further research is aimed at finding the most rational technical and organizational measures and their implementation in the city electric transport power supply system.
Keywords: urban electric transport; traction substations; regenerative braking; contact network; energy storage; measurements; experimental studies